MEWUJUDKAN DISIPLIN POSITIF DI SEKOLAH MELALUI KEPEMIMPINAN BERBASIS NILAI - Putri Mayadesti; Alfroki Martha; Iin Fekasuri; Adilla Yussianne (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to analyze and measure the effectiveness of implementing positive discipline in the school environment through values-based leadership policies. The research method used is quantitative by collecting numerical data through surveys and statistical analysis. Research respondents were students and teaching staff from schools that implemented positive discipline policies. The research variables involved measuring the level of implementation of positive discipline, students' perceptions of the effectiveness of the policy, and its impact on the learning environment. The research instrument is a questionnaire developed based on the concepts of positive discipline and values-based leadership. The results of data analysis will provide an overview of the extent to which values-based leadership policies can create positive discipline in schools. It is hoped that the implications of this research finding can contribute to the development of effective leadership models to create a conducive learning environment and support students' positive development. This research can also be a reference for schools, educational policy makers, and future researchers who are interested in developing positive discipline in the world of education.